20. \( x^{\frac{2}{3}}-5 x^{\frac{1}{3}}+6=0 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Let's solve the equation \( x^{\frac{2}{3}}-5 x^{\frac{1}{3}}+6=0 \). First, we can make a substitution to simplify it. Let \( y = x^{\frac{1}{3}} \), which transforms the equation into \( y^2 - 5y + 6 = 0 \). Next, this is a simple quadratic equation that can be factored as \( (y-2)(y-3)=0 \). So, the solutions for \( y \) are \( y = 2 \) and \( y = 3 \). Now, substituting \( y \) back to find \( x \): 1. If \( y = 2 \), then \( x^{\frac{1}{3}} = 2 \) gives \( x = 2^3 = 8 \). 2. If \( y = 3 \), then \( x^{\frac{1}{3}} = 3 \) gives \( x = 3^3 = 27 \). Thus, the solutions to the original equation are \( x = 8 \) and \( x = 27 \).